Israel inside [videorecording (DVD)] : how a small nation makes a big difference - Kopping, Wayne; Ben-Shahar, Tal (Passion River Films : Distributed by Gelb Productions, 2012)
Sidesteps the usual conversation of politics, conflict, and violence, and tells the story of the Israeli people - whose resilience has propelled Israel to the forefront of world innovation and progress. Hosted by former Harvard lecturer Dr. Tal Ben Shahar, this film explores the core characters strengths, called 'actualizers, ' that enable Israelis to succeed against incredible odds.